Prediction of genetic mutation from clinical data of sickle cell disease using few-shot siamese bidirectional LSTM and federated learning - Alam, Salman; Oni, Atquiya Labiba; Samir, Jubair; Hossain, Asif Mosharrof (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.